slides_Ch2_W[1]

# How can we do that first we need a random sample from

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: at? First we need a random sample from the population: f(yi , xi ) ji = 1, ..., ng. Observe that we can write yi = βo + β1 xi + ui for each i (2.9) How do we use this data? There exist several estimation procedures: Method of Moments Melissa Tartari (Yale) Econometrics 20 / 93 Three Estimation Methods Having established the key assumption under which ( βo , β1 ) are identi…able - ZCMA - we are now in the business of estimating these unknown parameters. How can we do that? First we need a random sample from the population: f(yi , xi ) ji = 1, ..., ng. Observe that we can write yi = βo + β1 xi + ui for each i (2.9) How do we use this data? There exist several estimation procedures: Method of Moments Least Squares Melissa Tartari (Yale) Econometrics 20 / 93 Three Estimation Methods Having established the key assumption under which ( βo , β1 ) are identi…able - ZCMA - we are now in the business of estimating these unknown parameters. How can we do that? First we need a random sample from the population: f(yi , xi ) ji = 1, ..., ng. Observe that we can write yi = βo + β1 xi + ui for each i (2.9) How do we use this data? There exist several estimation procedures: Method of Moments Least Squares Maximum Likelihood Melissa Tartari (Yale) Econometrics 20 / 93 The MoM: the Basics Observe that because of E [u jx ] = 0 we also have that E [ux ] = E [E [ux jx ]] = E [xE [u jx ]] = E [x 0] = 0. Melissa Tartari (Yale) Econometrics 21 / 93 The MoM: the Basics Observe that because of E [u jx ] = 0 we also have that E [ux ] = E [E [ux jx ]] = E [xE [u jx ]] = E [x 0] = 0. Thus, we have two moment conditions : E [u ] = 0 ) E [xu ] = 0 Melissa Tartari (Yale) E [y βo β1 x ] = 0 E [x (y βo β1 x )] = 0 Econometrics (2.12 & 2.13) 21 / 93 The MoM: the Basics Observe that because of E [u jx ] = 0 we also have that E [ux ] = E [E [ux jx ]] = E [xE [u jx ]] = E [x 0] = 0. Thus, we have two moment conditions : E [u ] = 0 ) E [xu ] = 0 E [y βo β1 x ] = 0 E [x (y βo β1 x )] = 0 (2.1...
View Full Document

## This note was uploaded on 02/13/2014 for the course ECON 350 taught by Professor Donaldbrown during the Fall '10 term at Yale.

Ask a homework question - tutors are online